2015
DOI: 10.1051/parasite/2015003
|View full text |Cite
|
Sign up to set email alerts
|

Pseudosuccinea columella: age resistance toCalicophoron daubneyiinfection in two snail populations

Abstract: Individual infections of Egyptian and French Pseudosuccinea columella with five miracidia of Calicophoron daubneyi were carried out to determine whether this lymnaeid was capable of sustaining larval development of this parasite. On day 42 post-exposure (at 23 °C), infected snails were only noted in groups of individuals measuring 1 or 2 mm in height at miracidial exposure. Snail survival in the 2-mm groups was significantly higher than that noted in the 1-mm snails, whatever the geographic origin of snail pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The observations in relation to C. daubneyi may be the consequence of the development, by the snails, of age-dependent resistance to the miracidial infection and/or the result of the stunted growth induced by the parasite larvae in susceptible snails. By means of experimental infections, Dar et al [43] demonstrated the existence of age-related resistance to C. daubneyi infection in the lymnaeid Pseudosuccinea columella : only the smallest snails of shell height ≤ 2 mm at miracidial exposure were able to sustain complete larval development of the parasite until cercarial shedding. Indeed, Rondelaud et al [19] observed that C. daubneyi caused more severe kidney damage than F. hepatica , in experimentally-infected snails.…”
Section: Discussionmentioning
confidence: 99%
“…The observations in relation to C. daubneyi may be the consequence of the development, by the snails, of age-dependent resistance to the miracidial infection and/or the result of the stunted growth induced by the parasite larvae in susceptible snails. By means of experimental infections, Dar et al [43] demonstrated the existence of age-related resistance to C. daubneyi infection in the lymnaeid Pseudosuccinea columella : only the smallest snails of shell height ≤ 2 mm at miracidial exposure were able to sustain complete larval development of the parasite until cercarial shedding. Indeed, Rondelaud et al [19] observed that C. daubneyi caused more severe kidney damage than F. hepatica , in experimentally-infected snails.…”
Section: Discussionmentioning
confidence: 99%
“…Low values noted for the overall prevalence of C. daubneyi infection in the 3 and 4 mm groups of P. columella may also be interpreted by the same explanation, i.e. the susceptibility of juveniles and the resistance of pre-adults to this parasite (Dar et al , 2015b).…”
Section: Discussionmentioning
confidence: 94%
“…Two other groups of 100 snails each, measuring 3 and 4 mm in shell height, respectively, were exposed only to five F. hepatica miracidia per snail and served as controls. No control group was constituted with C. daubneyi because all experimental infections of 3 and 4 mm snails carried out with this digenean were negative (Dar et al , 2015b). Snail exposure to miracidia and maintenance were similar to those applied in the first experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the experimental infection show that some amphistome species are more infective to a wider range of IH species, while others are specific to certain species. Of these, C. daubneyi (14,18,27,35,38,(55)(56)(57), C. microbothrium (16,(58)(59)(60), Z. lunata (61, 62), and P. cervi (63) infected multiple (≥4) IHs. According to Richards and Shade (64), genetic variations within and between species may account for the variability observed in the degree of infection of each amphistome species to different snail host species.…”
Section: Discussionmentioning
confidence: 99%